2015
DOI: 10.1097/fjc.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the Adenosine A2A Receptor Confers Pulmonary Arterial Hypertension Through RhoA/ROCK Signaling Pathway in Mice

Abstract: Numerous evidence suggests that RhoA/Rho kinase (ROCK) signaling pathway plays an important role in the pathogenesis of pulmonary arterial hypertension (PAH), but little is known about its effects on the development of PAH in mice with absence of the adenosine A2A receptor (A2AR). Eight A2AR knockout (KO) and 8 wild-type mice were used. Morphometric analysis of pulmonary arterioles included right ventricle/left ventricle plus ventricular septum (Fulton index), vessel wall thickness/total vascular diameter (WT%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…; Shang et al . ) may open new opportunities to unravel the mechanisms operated by A 2A R to control neurodegeneration.…”
Section: Signaling Mechanisms Underlying A2ar‐mediated Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…; Shang et al . ) may open new opportunities to unravel the mechanisms operated by A 2A R to control neurodegeneration.…”
Section: Signaling Mechanisms Underlying A2ar‐mediated Neurodegenerationmentioning
confidence: 99%
“…Interestingly, the evidence gathered in the last 20 years clearly speaks against this dogma of A 2A R signaling only or mainly through the cAMP-PKA pathway. In different tissues and cells, A 2A R activation has been shown to recruit and to signal through a variety of transducing pathways such as MAPK, namely ERK1/2 (extracellular signal-regulated kinases), p38 or c-Jun N-terminal kinases, PI-3K (phosphoinositide 3-kinase), protein phosphatases, protein kinase C, Src (acronym for sarcoma) kinases, or peroxisome proliferator-activated receptor, as illustrated by this non-exhaustive list of studies (Gubitz et al 1996;Revan et al 1996;Sexl et al 1997;Palmer and Stiles 1999;Seidel et al 1999;Gardner and Olah 2003;Murphy et al 2003;Boucher et al 2004;Fotheringham et al 2004;Gsandtner et al 2005;Pinto-Duarte et al 2005;Yu et al 2005;Melani et al 2006Melani et al , 2009Sun et al 2006Sun et al , 2010Che et al 2007;De Ponti et al 2007;Fresco et al 2007;Charalambous et al 2008;Tikh et al 2008;Canas et al 2009a,b;Simões et al 2012;Tamura et al 2012;Ahmad et al 2013;Nayeem et al 2013;Wang et al 2014;Zeidan et al 2014;Merighi et al 2015;Piirainen et al 2015;Shang et al 2015;Zhang et al 2015;Mohamed et al 2016).…”
Section: Signaling Mechanisms Underlying a 2a R-mediated Neurodegenermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the absence of adenosine signaling in A 2A receptor-knockout mice has been reported to be closely associated with the development of PAH, characterized by abnormal sclerosis/stenosis of distal pulmonary arteries due to increased smooth muscle proliferation and collagen deposition. By contrast, pharmacological activation of the A 2A receptor can partially reverse these pathological changes (11)(12)(13)(14). However, the detailed mechanisms that mediate the beneficial effects of adenosine signaling remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…currently, adenosine has been suggested as a potent pulmonary vasodilator, exerting beneficial effects in the amelioration of PAH (7)(8)(9)(10). In addition, experiments involving adenosine A(2A) receptor (A 2A receptor)-knockout mice indicated that A 2A receptor deficiency may also be involved in the development of PAH, characterized by increased smooth muscle proliferation and collagen deposition with abnormal sclerosis/stenosis of distal pulmonary arteries, whereas its pharmacological activation partially reversed these pathological changes (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%